Mutations That Alter the Transmission of Chloroplast Genes in Chlamydomonas - Sager, Ruth (1974)
Two mutations are described that alter the pattern of inheritance of chloroplast genes in Chlamydomonas. The mutant gene mat-1 linked to the mating type allele mt(-) greatly increases the frequency of exceptional zygotes, i.e., zygotes that transmit chloroplast genes from the mt(-) (male) parent. In some crosses, 80-90% of the zygotes are biparental, transmitting chloroplast genes from both parents. The mat-2 mutation, linked to mt(+), acts to decrease the frequency of exceptional zygotes below the spontaneous level. The mutant effects are discussed in terms of a DNA modification-restriction system, postulated to regulate the transmission of chloroplast DNA in zygotes.